2011
DOI: 10.18352/ijc.278
|View full text |Cite
|
Sign up to set email alerts
|

Resource intruders and robustness of social-ecological systems: an irrigation system of Southeast Spain, a case study

Abstract: Globalization increases the vulnerability of traditional socialecological systems (SES) to the incursion of new resource appropriators, i.e. intruders. New external disturbances that increase the physical and sociopolitical accessibility of SES (e.g. construction of a new road) and weak points Resource intruders and robustness of social-ecological systems 411 in institutional SES of valuable common-pool resources are some of the main factors that enhance the encroachment of intruders. The irrigation system of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Fines to irrigators caught stealing water may be reinforced during the dry season as a deterrent to free riding and to prevent situations potentially leading to the "tragedy of the commons" (Hardin 1968, Ostrom 1990). Water allocation rules may be temporarily modified to minimize the loss in bulk production, e.g., by giving irrigation priority to crops that are in most need of water (Maas and Anderson 1978), by promoting a temporary reduction in irrigated land (Pérez et al 2011), or by maximizing the net income per unit of water used rather than per land unit (Fereres and Soriano 2007). Adaptive water allocation rules and conflict-solving mechanisms governed by local institutions and communities are critical in ensuring the viability of these intensive agrarian areas over the long-term Many authors have characterized small-scale hydraulic systems as better endowed to achieve long-term survival in the face of uncertainty (Guijt and Thompson 1994, Mabry 1996a, b, Ertsen et al 2013.…”
Section: Commoning: the Case Of Andalusi Agriculturalistsmentioning
confidence: 99%
“…Fines to irrigators caught stealing water may be reinforced during the dry season as a deterrent to free riding and to prevent situations potentially leading to the "tragedy of the commons" (Hardin 1968, Ostrom 1990). Water allocation rules may be temporarily modified to minimize the loss in bulk production, e.g., by giving irrigation priority to crops that are in most need of water (Maas and Anderson 1978), by promoting a temporary reduction in irrigated land (Pérez et al 2011), or by maximizing the net income per unit of water used rather than per land unit (Fereres and Soriano 2007). Adaptive water allocation rules and conflict-solving mechanisms governed by local institutions and communities are critical in ensuring the viability of these intensive agrarian areas over the long-term Many authors have characterized small-scale hydraulic systems as better endowed to achieve long-term survival in the face of uncertainty (Guijt and Thompson 1994, Mabry 1996a, b, Ertsen et al 2013.…”
Section: Commoning: the Case Of Andalusi Agriculturalistsmentioning
confidence: 99%
“…These public infrastructures can be hard infrastructures such as dams and canals that reduce variance in benefit flows (link 4). The farmers of Caravaca aquifer in Spain, for instance, used to extract groundwater using traditional methods; however, because of population growth and commercialization of agriculture new farmers started to extract groundwater using regional government provided public infrastructures such as wells or reservoirs (Pérez et al 2011). Notably, these public infrastructures can also be soft infrastructures such as institutional arrangements that reduce unpredictability in human interactions with the environment (link 5).…”
Section: Research Framework and Data Sourcementioning
confidence: 99%
“…Furthermore, the environmental group 'Ecologistas en Acción' claimed that between 5,000 and 10,000 hectares of new illegal irrigation areas have annually been implemented in Murcia, which should be compared to the 192,000 hectares of legal irrigated land (Schouten, 2003). In a recent study, Perez et al (2011) showed that the effect of traditional irrigation systems in NW Murcia and the intrusion of new users, seriously affect groundwater levels and change the structure and robustness of the traditional social-ecological systems, thereby resulting in the emergence of new vulnerabilities.…”
Section: Institutions and Managementmentioning
confidence: 99%